Landcover Change Amidst Climate Change in the Lake Tana Basin (Ethiopia): Insights from 37 Years of Earth Observation on Landcover–Rainfall Interactions - Sullivan Tsay Fofang; Erasto Benedict Mukama; Anwar Assefa Adem; Stefaan Dondeyne (Remote Sensing)
Land use/landcover (LULC) changes and climate variability impact soil erosion; however, their combined long-term effects are poorly studied. Using remote sensing data, this study investigates changes in LULC and rainfall from 1985 to 2022 and their implications for soil erosion in the Lake Tana Basin, Ethiopia. The Global Land Cover Fine Classification System (GLC_FCS30D) data were used to analyze LULC changes; Climate Hazards Group InfraRed Precipitation with Station data (CHIRPS-v2) were used to assess rainfall trends; and the RUSLE was used to estimate potential soil erosion. The GLC_FCS30D proved to have an overall accuracy of 77.3% for 2005, 80.2% for 2014, and 80.3% for 2022. The cropland area increased slightly, from 32.9% to 33.3%, while tree cover initially decreased from 31.2% to 27.8% before recovering to 29.9%. Overall, annual rainfall increased by 2.92 mm yr−1, though it exhibited strong spatial variability, and rainfall erosivity rose by 1.25 MJ mm ha−1 h−1 yr−1. Despite seemingly modest changes in landcover and rainfall, the combined effect on potential soil erosion was substantial. Potential soil loss in the Lake Tana Basin showed significant spatial and temporal variation, with a slight increase of 0.9% from 1985 to 1995, followed by a slight decrease of 0.12% from 1995 to 2005, and a more substantial decrease of 2.3% from 2005 to 2015 before a notable increase of 8.2% occurred from 2015 to 2022. By elucidating the intricate interactions between landcover changes and rainfall variability, this study enhances our understanding of landscape dynamics in the Lake Tana Basin. The findings highlight the importance of considering the interaction between rainfall and landcover changes in climate change studies, as well as when targeting soil conservation efforts and promoting sustainable land management and ecosystem resilience in the tropics.